PENGARUH PENYELENGGARAAN HAJI TERHADAP PENINGKATAN AKTIVITAS EKONOMl DI WILAYAH PROPINSI DKI JAKARTA - Chairul Akmal (Al Qalam, 2013)
This research analyzes some factors affecting economic activities in relation with the conduct of pilgrimage. Those factors are the pilgrimage cost, the amount of pilgrims, and the amount of pilgrimage officers. The objective of this research is to acquire the information of how each factor and all factors together affect the economic activities. This research also analyzes the effect of foods and drinks expenses, the effect of nonfoods and drinks expenses, and the effect of miscellaneous expenses on UMKM - Micro, Small, Medium enterprises' economic activities. This research is conducted in DKI Jakarta in 2007. The population of this research is the average economic activities in DKI Jakarta in 2007. There are 42 respondents (Banks), 157 respondents (travel agencies), and 50 respondents (UMKM - Micro, Small, Medium enterprises) which are taken as samples from the population using the purposive sampling method. The data is obtained by the researcher using questioners and secondary data which is taken from 1990-2007. The methodology used in this research is based on. the causal relationship model In testing the hypothesis of this research, the researcher uses the simple and multiple regression methods, and path analysis method. The significant rate a = 0,05 used in determining the interpretation of the statistic result. The data is processed using SPSS (Statistical Packages for the Social Sciences) version 12.00. The results of the analysis in the 1st equation -are (i) the effect of the pilgrimage cost on banks' revenues is quite strong, (ii) the effect of the pilgrimage cost on travel agencies' revenues is quite strong, (iii) the effect of the pilgrimage cost on UMKM - Micro, Small, Medium enterprises' revenues is weak. The results of the analysis in the 2nd equation are (i) the effect, of the amount of pilgrims on Banks' revenues is very weak, (ii) the effect of the amount of pilgrims on travel agencies' revenues is very weak, (iii) the effect of the amount of pilgrims on UMKM - Micro, Smal4 Medium enterprises' revenues is very weak. The results of the analysis in the 3rd equation are (i) the effect of the amount of pilgrimage officers on banks' revenues is very weak, (ii) the effect of the amount of pilgrimage officers on travel agencies' revenues is very weak, (iii) the effect of the amount officers on UMKM-Micro, Small Medium enterprises' revenues is very weak. The results of the analysis in the 4th equation are (i) the effect of all three factors which are the pilgrimage cost, the amount of pilgrims, and the amount of pilgrimage officers simultaneously on banks' revenues is very strong, (ii) The effect of all three factors which are pilgrimage costs, the amount of pilgrims, and the amount of pilgrimage officers simultaneously on travel agencies' revenues is strong, (iii) The effect of all three factors which are pilgrimage costs, the amount of pilgrims, and the amount of pilgrimage officers simultaneously on UMKM-Micro, Small Medium enterprises' revenues is strong. The result of the analysis in the 5th equation is the effect of foods and drinks expenses on UMKM-Micro, Small Medium enterprises' revenues is weak. In the 6th equation, the effect of nonfoods and drinks expenses on UMKM-Micro, small Medium enterprises' revenues is weak. In the 7th equation, the effect of miscellaneous expenses on UMKM - Micro, Small Medium enterprises' revenues is quite strong. In the 8th equation, the effect of all three factors which are the effect of foods and drinks expenses, the effect of nonfoods and drinks expenses, and the effect of miscellaneous expenses simultaneously on UMKM-Micro, Small Medium enterprises' revenues is quite strong. The implication of the research results mentioned above is the factors in the conduct of pilgrimage do increase the economic activities (Banks, Travel Agencies, and UMKM - Micro, Smal4 Medium enterprises) in DKI Jakarta. Therefore, considering that matter, the General Director of the conduct of pilgrimage division of Department of Religion Republic of Indonesia should determine the pilgrimage cost which is affordable, increase the service, and provide a good information system which will result in a better conduct of the pilgrimage. Key word: The Costs of Hajj, Hajj Officer, Travel Agency, UMKM